Evidance Based Practice Osteoarthritis Melalui Penerapan Terapi Kompres Hangat terhadap Penurunan Intensitas Nyeri - Kampong, Miranti Nadini; Kairupan, Michelle Jessica; Karame, Verra (Yayasan Syalom Cipta Sumikolah, 2025)
A warm compress is a compress performed using a heated flask wrapped in cloth, which is conducted through conduction, where heat is transferred from the flask to the body, causing blood vessel dilation and reducing muscle tension, thus reducing or eliminating pain. The purpose of this research is to implement Gerontic Nursing Care for Mrs. M with Osteoarthritis Through the Application of Warm Compress Therapy to Reduce Pain Intensity at the Damai Ranomuut Nursing Home. This research, using evidence-based nursing, demonstrated the effectiveness of warm compresses in reducing gouty arthritis pain in Mrs. M for 3 days. The evaluation results showed that warm compresses were effective in reducing osteoarthritis pain in Mrs. M. There was a decrease in osteoarthritis pain in Mrs. M after the warm compresses were given. Hopefully, the results of this research will increase knowledge and the ability to provide nursing care to clients with osteoarthritis pain problems and be able to implement nursing interventions based on the Evidence-Based Practice approach.